Cyclic voltammetry study of reduced graphene oxide-PEDOT:PSS composite for electrochemical devices - Abdul Guthoos, Habibah Farhana; Ramli, Nurul Izzati; Wan Salim, Wan Wardatul Amani (IEEE, 2019)
Nanomaterials and conductive polymers have gained a great deal of interest for application in various fields, such as energy, the environment, and biomedicine, owing to their excellent physicochemical properties compared to conventional metal materials. A reduced graphene oxide (rGO)-poly(3,4 ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)- based electrode was fabricated via a simple physical drop-cast on electrodes followed by subsequent electrochemical reduction of GO to rGO. Cyclic voltammetry (CV) was used to characterize the redox capability of the composite layer on the electrode surface. Electrochemical deposition of rGO-PEDOT:PSS composites with a 1:1 ratio gives highest anodic peak current Ipa of 1.184 mA and largest effective surface area of 12.9 mm2, compared to bare and rGO electrodes. It appears that rGO-PEDOT:PSS composites could be an excellent material for the development of a redox-active electrode or transducer that can result in highly sensitive electrochemical-based devices.